Assessing Global Organ Donation Policies: Opt-In vs Opt-Out - Etheredge HR (Dove Medical Press, 2021)
Harriet Rosanne Etheredge1,2 1Wits Donald Gordon Medical Centre, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, South Africa; 2Steve Biko Centre for Bioethics, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, South AfricaCorrespondence: Harriet Rosanne EtheredgeWits Donald Gordon Medical Centre, 1st Floor, Max Price Building, 27 Eton Road, Parktown, Johannesburg, 2193, South AfricaTel +27 113566395Email harriet.etheredge@mediclinic.co.zaAbstract: This paper argues that there is little difference between opt-in and opt-out organ donation systems for increasing donor numbers when used in isolation. Independently diverting to an opt-out system confers no obvious advantage and can harm efforts to bolster donations. Rather, it is essential to address barriers to organ donation on several levels along with a switch in system. Moreover, for many countries, it may be more beneficial to adequately capacitate the donation system already in place, rather than entertain a significant change with its attendant resource requirements. For decades, the international transplant community has been involved in vigorous debate as to the merits of moving from default opt-in systems to opt-out policies to grow organ donor numbers and better meet the ever-increasing demand for lifesaving transplants. Opt-out is certainly en vogue, with Wales, England and Nova Scotia recently switching over, Scotland due to become opt-out in March 2021 and Northern Ireland and Canada seriously considering a similar move. Thanks to several countries making the switch from opt-in to opt-out over the last 20– 30 years, there are sets of robust longitudinal data that aid in analysing the efficacy of donation systems. However, these data are often contradictory and largely inconclusive, suggesting other factors may be in play. This paper reviews some emerging trends in opt-in versus opt-out organ donation policies and considers recent data that elucidates some of the main contentions across each. Ethical frameworks underpinning donation systems, such as informed consent, trust and transparency, are discussed in detail. Substantial time is also devoted to opt-in vs opt-out systems in developing countries, which tend to be excluded from many analyses, and where the challenges faced are magnified by socio-economic constraints. This constitutes a major gap in recently published literature, as developing countries often lag far behind their developed counterparts in donor and transplant numbers.Keywords: organ donation, opt-in, opt-out, consent, transparency, developing countries